Kajian tentang faktor-faktor yang mempengaruhi tingkah laku selamat dalam kalangan pekerja di sektor pembuatan - Ermie, Abdull Hamid (2017)
This study is to determine the influence of the five facets of Work Safety Scale (WSS) on compliance with safety behaviour among the employees in one of the manufacturing industries in Malaysia. A total of 130 questionnaires had been distributed to the sample chosen on the study which measures the workers’ perceptions on job safety, co-worker safety, supervisor safety, management safety, and satisfaction with safety program towards compliance with safety behaviour. All the results of measurement were then analyzed statistically with descriptive analysis of respondents’ background, reliability tests on variables’ internal consistencies, correlation, and regression analysis. This study revealed that supervisor safety is positively and significantly related to compliance with safety behaviour. Meanwhile, job safety, co-worker safety, management safety and satisfaction with safety program are not significantly related to compliance with safety behaviour. Therefore, it is hoped that the findings would be able to help researchers in their future research.